2007
DOI: 10.1016/j.anbehav.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Relative threat and recognition ability in the responses of tropical mockingbirds to song playback

Abstract: It has been suggested that individual recognition based on song may be constrained by repertoire size in songbirds with very large song repertoires. This hypothesis has been difficult to test because there are few studies on species with very large repertoires and because traditional experiments based on the dear enemy effect do not provide evidence against recognition. The tropical mockingbird, Mimus gilvus, is a cooperative breeder with very large song repertoires and stable territorial neighbourhoods. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…There are at least three reasons why large song repertoires may impose a constraint on individual recognition: (1) birds must learn more songs to facilitate discrimination; (2) each song type will be heard less frequently, creating less opportunity to learn each song; and (3) song sharing may be higher, making identity assignment more difficult (Stoddard, 1996). In contrast, other studies have found that some bird species capably discriminate between conspecific individuals despite their large repertoires (Botero, Riveros, & Vehrencamp, 2007;Hyman, 2005;Weary, Lemon, & Perreault, 1992). Additionally, two decades ago, a comparative analysis suggested that there was no relationship between repertoire size and neighbourestranger discrimination ability across 20 species of passerines of the suborder Passeri (Weary et al, 1992).…”
mentioning
confidence: 83%
“…There are at least three reasons why large song repertoires may impose a constraint on individual recognition: (1) birds must learn more songs to facilitate discrimination; (2) each song type will be heard less frequently, creating less opportunity to learn each song; and (3) song sharing may be higher, making identity assignment more difficult (Stoddard, 1996). In contrast, other studies have found that some bird species capably discriminate between conspecific individuals despite their large repertoires (Botero, Riveros, & Vehrencamp, 2007;Hyman, 2005;Weary, Lemon, & Perreault, 1992). Additionally, two decades ago, a comparative analysis suggested that there was no relationship between repertoire size and neighbourestranger discrimination ability across 20 species of passerines of the suborder Passeri (Weary et al, 1992).…”
mentioning
confidence: 83%
“…From August to December 2004 and from August 2005 to May 2006, we monitored 23 social groups of individually colour-banded tropical mockingbirds in Villa de Leyva, Colombia as part of an ongoing study on song learning and song use (Botero et al 2007). These social groups include 1.8 ± 0.20 males (mean ± SE) and 1.8 ± 0.16 females (data based on 19 groups for which molecular data is available).…”
Section: Methodsmentioning
confidence: 99%
“…Tropical mockingbirds live in cooperative breeding groups with multiple members of each sex that cooperate in the defence of a territory (Botero et al 2007; Morton et al 2004). Same-sex group members are organized in linear dominance hierarchies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that neighbouring territorial male songbirds share more song types than those with strangers, thus facilitating recognition between them (e.g. Botero et al 2007). However, we did not find any differences in shared song type between pairs of neighbouring males or stranger males, or that focal males use more song type matches to N-treatment than S-treatment playbacks (Table 2), since neighbours share only 1 song type, and strangers share 0.3.…”
Section: Recognition Systemmentioning
confidence: 99%